Percutaneous radiofrequency lesioning of the suprascapular nerve for the management of chronic shoulder pain: a case series - Thomas Simopoulos; Nagda; Aner (2012)
The objective of this study was to retrospectively evaluate the analgesic effects of continuous radiofrequency lesioning of the suprascapular nerve (SSN) for chronic shoulder pain. The authors sought to obtain insight into the time-sensitive analgesic success and complications of this therapy.This study was a retrospective case series involving patients with unremitting shoulder pain that had lasted for at least 12 months. Patients were selected if they showed a reduction of at least 50% in pain intensity during the anesthetic phase after SSN block, no additional motor weakness of the shoulder, and pain relief lasting for less than 2 months after separate treatments of the SSN with depot corticosteroids and pulsed radiofrequency. Nine patients were referred to the Arnold Pain Management Center. Of these nine patients, six patients who had significant chronic shoulder pain unresponsive to oral medications and intra-articular injections and who were not considered surgical candidates were selected. These patients were treated with a single radiofrequency lesion of the SSN at 80°C for 60 seconds. The primary outcome was a reduction in pain intensity by 50%, as determined by the numeric rating scale, and duration of this effect. The secondary outcome was improvement in either the passive or the active range of motion (ROM). Patients were also monitored for adverse effects such as weakness or increased pain.The pooled mean numeric rating scale score before the procedure was 7.2 ± 1.2; this fell to 3.0 ± 0.9 at 5-7 weeks post procedure. The duration of pain relief ranged from 3 to 18 months, and all patients underwent at least one additional treatment. The change in baseline ROM improved from an average of 60° ± 28° (flexion) and 58° ± 28° (abduction) to 99° ± 46° (flexion) and 107° ± 39° (abduction). No adverse side effects were observed.Continuous radiofrequency lesioning of the SSN seems to be an effective treatment for chronic shoulder pain. There can be improved ROM of the shoulder following this treatment. More formal, controlled studies are required to confirm these observations.